An International Comparative Study on The Performance of Big Data Transformation in The ‎Energy Industry: Empirical Analysis of Developing and Developed Economies - Cheng, Xinying (International Journal of Accounting and Economics Studies, 2025)
In the modern energy industry, the implementation of big-data technologies has taken the form of a ‎strategic necessity, as the requirements of digital efficiency, environmental sustainability, and ‎financial stability are being raised simultaneously. This paper is an empirical evaluation of the ‎effects of big-data adoption on financial performance and risk mitigation at the firm level and ‎focuses on publicly traded Chinese energy firms in 2015-2024. The aim is to measure the influence ‎of the digital maturity in three levels of transformation: pre, transition, and mature, and compare ‎these results against the known benchmarks of advanced economies. Using multi-method analytical ‎framework, including panel regression, difference-in-differences (DiD) estimation, analysis of ‎variance (ANOVA), and robustness testing using generalized method of moments (GMM) and ‎quantile regression, the current study evaluates the following three outcomes: profitability (EBIT ‎margin), financial stability (Altman Z-Score), and bankruptcy risk (Ohlson O-Score). The findings ‎show that the performance of the corporation increases over the years: the EBIT margin increases by ‎‎2.48 percentage points and the Z-Score by 0.38 points, during the mature stage, and the O-Score ‎decreases by 0.80 points. A sectoral analysis shows that electric power firms are the most ‎responsive, with less-pronounced gains in coal firms. Together, the results provide substantial ‎support that the big data transformation enhances operational efficiency and financial strength, and ‎has ramifications on strategic investment, policy development, and digital modernization in the ‎emerging and developed energy markets‎.